Relationship marketing strategy: the pathway to relational orientation through customer symbiosis - Chokera, Fainos; Duve, Richard (Booklove Publishers, 2022)
This book aims to provide insight into the understanding of current paradigms of symbiosizing relationships through networking and netweaving.